Dopamine Homeostasis Imbalance and Dopamine Receptors-Mediated AC/cAMP/PKA Pathway Activation are Involved in Aconitine-Induced Neurological Impairment in Zebrafish and SH-SY5Y Cells - Zhou, Jie; Peng, Cheng; Li, Qiuju; Yan, Xiaoyu; Yang, Liang; Li, Mengting; Cao, Xiaoyu; Xie, Xiaofang; Chen, Dayi; Rao, Chaolong; Huang, Sizhou; Peng, Fu; et al. (Frontiers in Pharmacology, 2022)
Aconitine is one of the main bioactive and toxic ingredients of Aconitum species. Increasingly, aconitine has been reported to induce neurotoxicity. However, whether aconitine has effects on the dopaminergic nervous system remains unclear. In this study, zebrafish embryos at 6-days postfertilization were exposed to aconitine at doses of 0.5, 1, and 2 μM for 24 h, and SH-SY5Y cells were treated with 50, 100, and 200 μM of aconitine for 24 h. Results demonstrated that aconitine treatment induced deformities and enhanced the swimming behavior of zebrafish larvaes. Aconitine exposure suppressed cell proliferation and increased the number of reactive oxygen species and apoptosis in zebrafish larvaes and SH-SY5Y cells. Aconitine altered the levels of dopamine and its metabolites by regulating the expression of genes and proteins related to dopamine synthesis, storage, degradation, and reuptake in vivo and in vitro. Moreover, aconitine activated the AC/cAMP/PKA pathway by activating the dopamine D1 receptor (D1R) and inhibiting the dopamine D2 receptor (D2R) to disturb intracellular calcium homeostasis, eventually leading to the damage of nerve cells. Furthermore, the D1R antagonist SCH23390 and D2R agonist sumanirole pretreatment effectively attenuated the excitatory state of larvaes. Sumanirole and PKA antagonist H-89 pretreatment effectively decreased intracellular Ca2+ accumulation induced by aconitine in vivo. SCH23390 and sumanirole also reduced aconitine-induced cytotoxicity by inhibiting the AC/cAMP/PKA pathway in vitro. These results suggested that dopamine homeostasis imbalance and dopamine receptors (DRs)-mediated AC/cAMP/PKA pathway activation might be vital mechanisms underlying aconitine-induced neurological injury.